Rural community adult literacy development through community learning centers program in the Islamic Republic of Iran: two case studies - Zolfaghari, Akbar; Sabran, Mohammad Shatar; Zolfaghari, Azam (Scientia Socialis, 2009)
Literacy and community development have an unbroken connection. Literacy is a very important tool for community development. The main goal of community development is to improve the quality of life. In order to improve the quality of life, the government of Iran has implemented several programs to promote the level of literacy. CLCP is the newest and the most important literacy program in Iran post revolution that has been introduced by the Iran’s Development Plans. It has been emerged as a result of shortcomings of the previous literacy programs to solve the problem of illiteracy in the country. Therefore, the general objective of this study was to examine the role of the program in rural community adult literacy development while the specific objective of this study was to describe the factors contributed to the success of the program in Iran. For the purpose, two rural communities namely Golshan and Nasr Abad into two different states of Kerman and Yazd in Iran were selected as the case studies. The selection was based on their literacy level. The community with the lowest literacy level in each state was chosen.